2018
DOI: 10.1371/journal.pone.0204803
|View full text |Cite
|
Sign up to set email alerts
|

Lack of vitamin D signalling per se does not aggravate cardiac functional impairment induced by myocardial infarction in mice

Abstract: Epidemiological studies have linked vitamin D deficiency to an increased incidence of myocardial infarction and support a role for vitamin D signalling in the pathophysiology of myocardial infarction. Vitamin D deficiency results in the development of secondary hyperparathyroidism, however, the role of secondary hyperparathyroidism in the pathophysiology of myocardial infarction is not known. Here, we aimed to explore further the secondary hyperparathyroidism independent role of vitamin D signalling in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(67 reference statements)
0
4
0
1
Order By: Relevance
“…Stimulation of heart regeneration in mammals by secreted factors may be more complex than in zebrafish, as mammalian adult CMs have a lower proliferative capacity and/or more hurdles to division like polyploidy (Gonzalez-Rosa et al, 2018;Patterson et al, 2017). Vitamin D signaling has been reported to protect mouse CMs from pathological hypertrophy by regulation of calcium handling (Chen et al, 2011;Choudhury et al, 2014;Ford et al, 2018), but we have identified no clear evidence from published literature for hyperplastic effects in mammalian hearts. To examine potential effects on cultured mouse P7 CMs, we treated with different concentrations of calcitriol and examined the expression of the proliferation marker Ki67 after 3 days.…”
Section: Vitamin D Signaling Regulates Heart Regenerationmentioning
confidence: 77%
“…Stimulation of heart regeneration in mammals by secreted factors may be more complex than in zebrafish, as mammalian adult CMs have a lower proliferative capacity and/or more hurdles to division like polyploidy (Gonzalez-Rosa et al, 2018;Patterson et al, 2017). Vitamin D signaling has been reported to protect mouse CMs from pathological hypertrophy by regulation of calcium handling (Chen et al, 2011;Choudhury et al, 2014;Ford et al, 2018), but we have identified no clear evidence from published literature for hyperplastic effects in mammalian hearts. To examine potential effects on cultured mouse P7 CMs, we treated with different concentrations of calcitriol and examined the expression of the proliferation marker Ki67 after 3 days.…”
Section: Vitamin D Signaling Regulates Heart Regenerationmentioning
confidence: 77%
“…Bae and coworkers reported detrimental effects of global VDR deficiency after experimental MI induced by permanent ligation of the left descending coronary artery in global VDR knock-out mice fed a normal diet [ 72 ]. By contrast, cardiac function after experimental MI was not different between normocalcemic VDR mutant mice on the rescue diet and wild-type mice [ 73 ]. Therefore, the detrimental effects of global VDR deficiency in MI mice may be attributed to hypocalcemia and secondary hyperparathyroidism [ 73 ].…”
Section: Atherosclerosismentioning
confidence: 99%
“…By contrast, cardiac function after experimental MI was not different between normocalcemic VDR mutant mice on the rescue diet and wild-type mice [ 73 ]. Therefore, the detrimental effects of global VDR deficiency in MI mice may be attributed to hypocalcemia and secondary hyperparathyroidism [ 73 ].…”
Section: Atherosclerosismentioning
confidence: 99%
“…In contrast, we observed no difference in the hypertrophic response of wild-type (WT) mice and those lacking VDR globally subjected to transverse aortic constriction (TAC), a standard model of experimental LVH induced by chronically increased afterload [22]. In addition, we found no difference in heart function between WT mice and global VDR knockout mice after myocardial infarction in an earlier study [23].…”
Section: Introductionmentioning
confidence: 59%